|1||x + 3 = 5||This is the equation to simplify.|
|2||x + 3 - 3 = 5 - 3||Subtract 3 from both sides. The 3 - 3 on the left side of the equation is a zero sum.|
|3||x + 0 = 2||Simplify the constant terms|
|4||x = 2||Apply the additive property of zero to transform x + 0 to x. This is the solution.|
All Math Words Encyclopedia is a service of
Life is a Story Problem LLC.
Copyright © 2005-2011 Life is a Story Problem LLC. All rights reserved.
This work is licensed under a Creative Commons Attribution-Noncommercial-Share Alike 3.0 License